CNT addition to the LiBH4-MgH2 composite: the effect of milling sequence on the hydrogen cycling properties - Cova, Federico Hector (2015)
The composite 2LiBH4 : MgH2 has recently received attention as a potential hydrogen storage material. This is mainly due to its high storage capacity. However, the temperatures needed to obtain adequate reaction kinetics are still too high for practical applications. In the present work we study the effect of Ni and carbon nanotube addition as catalysers. We found that different synthesis methods of the composite lead to different hydrogen absorption/desorption kinetic behaviours. These changes can be attributed to morphological and microstructural differences caused by the dissimilar milling stages at which the nanotubes were introduced during the sample synthesis. An induction time during the hydrogen desorption appeared as a consequence of the different dispersions of the carbon nanotubes observed in the samples prepared with both synthesis methods. It was also found that equilibrium pressure increased when the temperature decreased below 375 °C, this effect was kinetic and it was possible to conclude that the addition of nanotubes had no effect on the thermodynamics of the system.